Insulin-containing lipogenic stimuli suppress mast cell degranulation potential and up-regulate lipid body biogenesis and eicosanoid secretion in a PPARγ-independent manner - Greineisen, William E. (Society for Leukocyte Biology, 2012)
Lipid bodies are most studied in adipocytes, where the lipogenic action of insulin initiates their formation. Here, we test the hypothesis that insulin may regulate lipid body content in mast cells and hence, modify their proinflammatory potential. Our data show that insulin causes lipid body accumulation in RBL2H3 and BMMCs. Lipid body accumulation in mast cells is associated with enhanced levels of leukotriene-synthesizing enzymes (LTC4S and 5-LO). Increased basal and antigen-stimulated release of LTC4 is observed in insulin-treated mast cells. Concomitantly, the insulin-containing lipogenic stimulus induces a phenotypic change in mast cells, where this enhancement in leukotriene levels is accompanied by a marked down-regulation in secretory granule content and release in response to stimulus. Mast cells exposed to insulin exhibit altered scatter and fluorescence properties, accumulating in a SSC(lo)FSC(hi) population that exhibits decreased BS staining and degranulation responses and is enriched in NR-positive lipid bodies and eicosanoid synthesis enzymes. Lipid body accumulation in mast cells is mechanistically distinct from the process in adipocytes; for example, it is independent of PPARγ up-regulation and does not involve significant accumulation of conjugated glycerides. Thus, chronic exposure to metabolic stimuli, such as insulin, may be a determinant of the proinflammatory potential of the mast cell.